ATTITUDES OF INDIGENOUS ACEHNESE PEOPLE TOWARDS THEIR VERNACULAR MAINTENANCE IN LANGSA. - Fakhrurrazi, Fakhrurrazi (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2016)
This research is a study on native people’s attitudes towards Acehnese language in Langsa Aceh. The research design used a qualitative research method that examines the attitudes of native speakers of the language of Aceh in Langsa in prewserving the language. The subject of research is the native speakers of Acehnese who live in the city of Langsa from eighteen years to twenty years old. This study used observation, questionnaire and interview. The data obtained from this study were analyzed based on the cooperative model intrcidued by Miles and Hubermann. The study shows that 55% of respondents indicates a very positive attitude towards in preserving the Acehnese by using the language in everyday communication. While 45% of respondents indicates a negative attitude where they seldom use Acehnese in their daily interaction and very often switch the language to Indonesian in their communication. The study also reveals that the use of Acehnese at home, the pride of using Acehnese and the Acehnese as identity are the factors that contribute to the preservation of Acehnese.